Profil Pemecahan Masalah Aljabar Berpandu Pada Taksonomi SOLO Ditinjau Dari Gaya Kognitif Konseptual Tempo Siswa SMA Negeri 1 Makale Tana Toraja [A Profile of Guided Algebra Problem Solving Using the SOLO Taxonomy and the Cognitive Conceptual Tempo Style of Students at the SMA Negeri 1 School In Makale, Tana Toraja] - Oce Datu Appulembang (Polyglot, 2017)
The objective of this research was to discover the process used in solving a superitem test which consisted of 4 stages according to the SOLO (Structure of Learning Outcomes) Taxonomy, namely unistuctural, multistructural, relational, and extended abstract, and reviewed using the cognitive impulsive and reflective style. The research was qualitative research. The main instrument of the research was the researcher himself guided by a superitem test, an impulsive-reflective cognitive test namely MFFT (Matching Familiar Figure Test), and a valid interview guideline. The subject of this research was the students of class X1 at SMA Negeri 1 Makale Tana Toraja consisting of four students in which 2 subjects were with cognitive impulsive style and 2 subjects with cognitive reflective style. The data was collected by giving a superitem test which was verified with an interview. The results of the research show that: (a) the first subject’s impulsive and reflective style showed the tendency of problem solving at an abstract level which was expanded in the question of one variable linear equation and in the question of two variable linear equation, (b) the second subject’s impulsive cognitive style in two variable linear equation problem solving showed the tendency of unistuctural and relational thinking only, (c) the second subject’s cognitive reflective style showed the tendency of problem solving in relational level, (d) the subject’s impulsive and reflective cognitive style showed the tendency of the same problem solving in the level unistructural, multistructural, relational, and abstract in the question of one variable linear equation, and different in the abstract level in the question of two variable linear equation.BAHASA INDONESIA ABSTRAK: Tujuan penelitian ini adalah untuk mengetahui profil pemecahan masalah dengan melihat dan mengungkap proses berpikir siswa dalam menyelesaikan tes superitem yang terdiri atas 4 tingkatan menurut Taksonomi SOLO (Structure of Observed Learning Outcomes), yaitu: unistruktural, multistruktural, relasional, dan abstrak yang diperluas ditinjau dari gaya kognitif impulsif dan reflektif. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Instrumen utama dalam penelitian ini adalah peneliti sendiri yang dipandu oleh tes superitem, tes gaya kognitif impulsif-reflektif, yaitu: MFFT (Matching Familiar Figure Test), dan pedoman wawancara yang valid. Subjek penelitian ini adalah siswa kelas X1 SMA Negeri 1 Makale Tana Toraja yang terdiri dari 4 subjek yang mana 2 subjek gaya kognitif impulsif dan 2 subjek gaya kognitif reflektif. Pengumpulan data dilakukan dengan pemberian tes superitem dan verifikasi dengan wawancara. Hasil penelitian ini adalah (a) Subjek pertama gaya kognitif impulsif (GKI) maupun reflektif (GKR) menunjukkan kecenderungan pemecahan masalah pada tingkat abstrak yang diperluas pada soal persamaan linear satu variabel dan soal persamaan linear dua variabel, (b) Subjek kedua gaya kognitif impulsif pada pemecahan masalah persamaan linear dua variabel menunjukkan kecenderungan berpikir unistruktural dan relasional saja, (c) Subjek kedua gaya kognitif reflektif (GKR) menunjukkan kecenderungan pemecahan masalah pada tingkat relasional, (d) Subjek gaya kognitif impulsif maupun reflektif menunjukkan kecenderungan pemecahan masalah yang sama pada tingkat unistruktural, multistruktural, relasional dan abstrak pada soal persamaan linear satu variabel, dan berbeda pada tingkat abstrak pada soal persamaan linear dua variabel.